Current status and influencing factors of activation of older patients with chronic disease - Yiran, Zhu; Yan, Zhang; Lijun, Xing; Xizheng, Li; Xinjie, Zhang; Yutong, Tian (Frontiers in Public Health, 2024)
Objective We aimed to investigate the status and influencing factors of activation of elderly patients with chronic disease.We conducted a cross-sectional study, using the general information questionnaire, Patient Activation Measure, Chinese version of e-Health Literacy Scale, Health Empowerment Scale for Elderly with Chronic Disease. By the convenience sampling method, 289 elderly patients with chronic disease were selected from January to April 2023 in a Class A tertiary hospital in Zhengzhou.The mean score of the Patient Activation Measure for elderly patients with chronic disease was (65.94 ± 13.35). The association of influencing factors such as religion, family income, health empowerment, and e-health literacy and patient activation was investigated.The patient activation of elderly patients with chronic disease was at a middle level.Patients without a religion and from high income families tended to have a higher level of patient activation. Improving health empowerment and e-health literacy level promotes patient activation and enhances their self-health management ability.